House of spies - Silva, Daniel, 1960- (Silva, Daniel, 1960- Gabriel Allon series., 2017)
Four months after the deadliest attack on the American homeland since 9/11, terrorists leave a trail of carnage through London<U+2019>s glittering West End. The attack is a brilliant feat of planning and secrecy, but with one loose thread. The thread leads Gabriel Allon and his team of operatives to the south of France and to the gilded doorstep of Jean-Luc Martel and Olivia Watson. A beautiful former British fashion model, Olivia pretends not to know that the true source of Martel<U+2019>s enormous wealth is drugs. And Martel, likewise, turns a blind eye to the fact he is doing business with a man whose objective is the very destruction of the West. Together, under Gabriel<U+2019>s skilled hand, they will become an unlikely pair of heroes in the global war on terror.